The Upaya Guru PAI Membentuk Konsep Diri Pribadi pada Siswa di MI Sullamul Hidayah Samarinda - Alya Fadila; Achmad Ruslan Afendi (Departement of Mathematics Education, 2023)
Efforts of PAI Teachers in Forming Muslim Personal Self-Concepts in Students at MI Sullamul Hidayah Samarinda. In Islam, personality is a very important factor. In this day and age many students forget their identity as a Muslim. Like the lack of politeness towards teachers, speaking harshly, not used to thinking greetings and so on. The purpose of this study was to find out the efforts of PAI teachers in forming Muslim personalities in students at MI Sullamul Hidayah Samarinda. The type of research used in this research is descriptive qualitative. The population in this study was 1 PAI teacher at MI Sullamul Hidayah Samarinda. Data collection techniques in this study were interviews and documentation. Based on the results of the study, it was stated that the efforts of PAI teachers in forming Muslim personalities for students at MI Sullamul Hidayah Samarinda were by carrying out various religious programs, providing examples, and habituating them in everyday life.